Outcome of Teenage Pregnancy Associated with Medical Conditions - Sultana, Nigar; Huq, Syed Rezaul; Parvin, Tabassum; Hussain, M Anwar; Rahaman, Md Abedur (Journal of Shaheed Suhrawardy Medical College, 2012)
Objective: This study was carried out to evaluate the Maternal and fetal outcome of teenage Pregnancy with different medical conditions during Pregnancy in the selected high risk hospital population of Bangladesh. Methods: This was a cross sectional study. The study was done on 50 (fifty) teenage pregnant adolescent admitted in the Dhaka medical college Hospital and Bangabandhu sheikh Mujib Medical University Hospital during the study period July 2004 to June 2005. Samples were selected randomly from the admitted patients. Results: Seventy five percent of the mother had complication during delivery, of them 21.42% had PPH, 14.28% had inadequate lactation, 10.71% had post partum eclampsia, another 10.71% had wound dehiscence, 7.14% had post spinal headache. Eighty four percent of the babies were alive, of them Forty percent required resuscitation. Ten percent were dead and 6% were still born. Fourty eight percent of the new born had birth weight less than 2.5 kg, 32% had more than 2.5kg. APGAR score at one minute varied between 5-7 in 75% of cases and was 8-9 in 22.5%. Only 2% has <5. APGAR score at five minutes varied between 8-9 in 92.5% of cases. 40% of the babies developed jaundice, 30% babies were birth asphyxiated, IUGR 8%, prematurely 6%, congenital anomalies 4%. Conclusion: Outcome of teenage pregnancy with medical conditions is poor. DOI: http://dx.doi.org/10.3329/jssmc.v1i2.12159 Journal of Shaheed Suhrawardy Medical College Vol.1, No.2, December 2009 p.10-13